SENI DAN DESAIN YANG MINIM PENELITIAN - Farid Abdullah (Jurnal Dimensi Seni Rupa dan Desain, 2013)
AbstractIn short this book is called " visualizing reserach". The book 's content is how to learn to make a research, especialy in Art and Design studies. The introduction of the book, aims to guide postgraduate students in Art and Design through the research process, an it might be used in conjuction with a formal study programme.This book explains how to make a rsearch in master to do doctoral level, from the storage of development until implementation of a research process. The most important points from this book are that every researcher must require three things: Passion, self-confidence, and method AbstrakSecara singkat buku ini disebut  sebagai " memvisualkan penelitian" . Buku ini membahas bagaimana belajar dalam suatu penelitian, khususnya di bidang Seni dan Desain. tujuan yang tercantum dalam pengantar buku ini adalah untuk memandu para peserta didik pasca sarjana di bidang Seni dan Desain, melalui sebuah proses penelitian dan buku ini juga dapat dipergunakan pada sebuah program  syudi formal. Buku ini menjelaskan bagaimana membuat sebuah penelitian dari ingkat magister (S2) hingga doktoral (S3) Seni dan Desain. Dari tahap pengembangan hingga tahap penerapan dari sebuah proses penelitian.